Output Gap Uncertainty and Real-Time Monetary Policy - Grigoli, Francesco (IMF Working Papers; Working Paper, 2015)
Output gap estimates are subject to a wide range of uncertainty owing to data revisions and the difficulty in distinguishing between cycle and trend in real time. This is important given the central role in monetary policy of assessments of economic activity relative to capacity. We show that country desks tend to overestimate economic slack, especially during recessions, and that uncertainty in initial output gap estimates persists several years. Only a small share of output gap revisions is predictable ex ante based on characteristics like output dynamics, data quality, and policy frameworks. We also show that for a group of Latin American inflation targeters the prescriptions from typical monetary policy rules are subject to large changes due to output gap revisions. These revisions explain a sizable proportion of the deviation of inflation from target, suggesting this information is not accounted for in real-time policy decisions.